How Smart Supply Chain Management Solves Logistics Bottlenecks at Mixue Bandung - Dedi Hadian; Aan Hardiyana; Senen Machmud; Maulana Yusup; Anton Tirta Komara; Bulan Tati Fitria; Robbi Saepul Rahman; Carolina Tanu Sukria; Ziera Eliya; Muhammad Rikfi Ramadhan; Faizal Ramdhan Permana; Gerald Nathaniel (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The research aims to evaluate and optimize the integration of Supply Chain Management (SCM) to boost regional logistics efficiency. To achieve this purpose, the research team—comprising both lecturers and students—adopts a qualitative research methodology. The team gathers primary empirical data by conducting direct field observations and structured interviews with operational workers who manage day-to-day logistics and store processes. For data analysis, the team utilizes a qualitative thematic analysis technique, which involves transcribing interview recordings, coding field notes, categorizing data into core operational themes, and synthesizing the results to formulate concrete solutions. The findings reveal that Mixue's strict closed supply chain system successfully maintains uniform product quality and secures low product-rejection rates across all Bandung outlets. Furthermore, the integration of real-time Point of Sales (POS) data with central SCM systems eliminates transaction errors and effectively eradicates stockout occurrences.